Dinamika Perumusan Pasal dalam Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual Terkait Pemaksaan Perkawinan - Jannah, Wildatul; Pratama, Aman; Gabryella, Gabryella; Matippanna, Rimayun; Nugraha, Septian Adi; Al Hafiz, Si Yusuf (Jurnal Restorasi Hukum, 2023)
Abstract: Forced marriage is a complex phenomenon that describes the interaction between norms, religion, culture, law and human rights. This practice has been going on for a long time in Indonesia, such as the Lily marriage tradition in West Nusa Tenggara, marriage due to pregnancy/rape, early marriage and others. This research will explore how the regulations regarding forced marriage have been integrated into Law No. 12 of 2022 concerning the Crime of Sexual Violence, as well as their impact on the legal and political framework. The introduction will provide background on the steps taken by the TPKS Law from the time it was initiated until it was passed into law, as well as the actors involved in the process of formulating the law. The research method used is normative empirical. The research uses legal, social and cultural debates that arise in the context of forced marriage under Law Number 12 of 2022 concerning TPKS. Policy implications emerging from the research include consideration of the balance between recognition of cultural values and protection of human rights within the relevant legal framework. Abstrak: Pemaksaan perkawinan adalah fenomena kompleks yang menggambarkan interaksi antara norma, agama, budaya, hukum dan Hak Asasi Manusia. Praktik ini telah berlangsung lama di Indonesia, seperti tradisi kawin Lily di Nusa Tenggara Barat, perkawinan karena kehamilan/pemerkosaan, perkawinan dini dan lainnya. Penelitian ini akan menggali bagaimana aturan terkait pemaksaan perkawinan tersebut telah diintegrasikan dalam Undang-Undang No 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual, serta dampaknya terhadap kerangka hukum dan politik. Pendahuluan akan menyajikan latar belakang tentang jejak langkah UU TPKS dari saat dicetuskan hingga disahkan menjadi UU, serta aktor yang terlibat dalam proses perumusan UU. Metode penelitian yang digunakan yakni normatif empiris. Penelitian menggunakan perdebatan hukum, sosial, budaya yang muncul dalam konteks pemaksaan perkawinan di bawah UU Nomor 12 Tahun 2022 tentang TPKS. Implikasi kebijakan yang muncul dari penelitian mencakup pertimbangan keseimbangan antara pengakuan terhadap nilai budaya dan perlindungan HAM dalam kerangka hukum yang relevan.